Voice priority queue scheduling system models for VoIP over WLANs - Nisar, Kashif (IGI Global - All Rights Reserved, 2013)
The Voice over Internet Protocol (VoIP) is a delay sensitive traffic due to real-time applications on networks.The assessment of voice flow quality in the VoIP is an essential requirement for technical and commercial motivation.The packets of VoIP streaming may experience drops because of the competition among the different kinds of traffic flow over the network. A VoIP application is also sensitive to delay and requires the voice packets to arrive on time from the sender to the receiver side without any delay over WLAN.The scheduling system model for VoIP traffic is an unresolved problem.In this research paper, the author proposes a new Voice Priority Queue (VPQ) scheduling system models and algorithms for the VoIP over WLANs to solve scheduling issues over IP-based networks.They present new contributions, through the three stages of the VPQ.The VPQ scheduling algorithm is provided as an essential technique in the VoIP communication networks to guarantee the QoS requirements.The design of the VPQ is managed by the limited bandwidth utilization and has been proven to have an efficient performance over WLANs.